Journal of clinical bioinformatics
"JCBi aims to elucidate how biological and medical information can be applied to the development of personalized healthcare, medication and therapies. JCBi is a forum for the translation of bioinformatics and computational methods into clinical and medical applications, as well as the advancement of our understanding of the molecular and cellular mechanisms of diseases. "